The Effect of Human and Spatial Crowding on Repurchase Intention in Restaurant Using Brand and Customer Satisfaction as a Mediation Variable - Ulinnuha, Husna; Setiawan, Budi; Isaskar, Riyanti; Wahyuningtyas, Agustina Shinta Hartati (HABITAT, 2025)
Crowding in the physical environment of restaurants are common in popular restaurants. Human crowding refers to the large number of visitors in the restaurant. And spatial crowding refers to the dense physical environment of a restaurant, such as a large number of tables and chairs and decorations or restaurant design ornaments that are dense enough to make the restaurant look narrower. Through this density and crowding, restaurants must provide a good image or reputation to increase consumer attachment, satisfaction, and repurchase intentions. Data was collected using an online questionnaire and distributed to 200 respondents from spicy noodle restaurant consumers. Furthermore, data analysis uses SEM-PLS (Structural Equation Modeling - Partial Least Square) with the help of WarpPLS 8.0 software. The results showed that human and spatial crowding affects brand image, brand image affects brand attachment and customer satisfaction, brand attachment and customer satisfaction affect repurchase intention, and human and spatial crowding influence repurchase intention through brand image, brand attachment, and customer satisfaction as mediation. Based on this study's results, the operant hoped that the restaurant can determine strategies by considering variables and indicators that can increase customer satisfaction and repurchase intentions.